Analisis Pengaruh Keadilan Pajak Dan Sistem Perpajakan Terhadap Tax Evasion - Elia Rossa; Lissa Rahmawati; Muh Farhan Yudamahendra; Muhammad Rivki Adrian; Nabila Syifaa Azzahra Suwandi; Neyla Safitri; Vina Hariyati (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
Taxpayers' perceptions regarding coercive taxes have a negative impact on taxpayers to reduce their tax burden by carrying out tax avoidance. But the fact is that this method is difficult to implement, making taxpayers prefer to commit tax evasion. It is believed that tax justice and the tax system can influence corporate and individual taxpayers to carry out illegal tax avoidance activities or tax evasion. This research was conducted to determine the influence of Tax Justice and the Tax System on Tax Evasion. This research was carried out using qualitative methods with literature studies and literature reviews, the results obtained were that tax justice and the tax system had a negative effect on tax evasion